Quimiometria aplicada à análise de embalagens plásticas na indústria alimentícia - Almeida, Heloísa Nascimento de (Universidade Federal de São Carlos, 2022)
Most of the packaging used in the food sector is produced in plastic materials that can be flexible or rigid. Rigid packaging such as high-density polyethylene is highlighted because they keep their shape independent of the characteristics of the stored product, however, under certain conditions, they are susceptible to deformation during storage, transport, and stacking. Therefore, in order to evaluate a possible decrease in the weight of the packaging aiming at productivity aspects, chemometric tools were used to understand how the storage temperature and the weight of the packaging affect in the resistance to compression and deformation. With the application of statistical tools such as Pearson coefficient, variance analysis and Tukey test it was possible to verify that the temperature and the weight of the packaging influence the mean of resistance, however only weight is a statistically significant factor for the mean of deformation.
Chemometrics applied to the analysis of plastic packaging in the food industry
Keywords: Embalagens; Quimiometria; PEAD; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::INSTRUMENTACAO ANALITICA